2018
DOI: 10.1364/oe.26.003435
|View full text |Cite
|
Sign up to set email alerts
|

Resonantly pumped eye-safe Er3+:YAG SPS-HIP ceramic laser

Abstract: We report for the first time laser action in resonantly-pumped transparent polycrystalline Er:YAG ceramic developed through a 2-step approach combining spark plasma sintering and HIP post treatment. Microstructural and spectroscopic properties, as well as the laser performance of large scale 0.5at.% Er:YAG transparent polycrystalline ceramic are discussed. A maximum slope efficiency of ∼31% and optical-optical efficiency of 20% was measured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Bigotta et al [48] reported laser operation in 0.5 at.% Er 3+ -doped YAG polycrystalline ceramics developed by SPS starting from commercial precursor powder size of 271 nm. After obtaining SPS samples, they were treated with hot isostatic pressing (HIP), which helps in obtaining highly transparent ceramics and removing porosity.…”
Section: Transparent Ceramicsmentioning
confidence: 99%
“…Bigotta et al [48] reported laser operation in 0.5 at.% Er 3+ -doped YAG polycrystalline ceramics developed by SPS starting from commercial precursor powder size of 271 nm. After obtaining SPS samples, they were treated with hot isostatic pressing (HIP), which helps in obtaining highly transparent ceramics and removing porosity.…”
Section: Transparent Ceramicsmentioning
confidence: 99%
“…[3] Spark plasma sintering (SPS), also commonly referred to as field-assisted sintering technology, is a rapid single-step densification technique [21] that keeps growing in popularity while being extended toward more advanced materials. [22] Regarding transparent ceramics, SPS has been successfully used to fabricate various laser ceramics, such as Nd 3þ :Lu 2 O 3 , [23] Yb 3þ :Y 2 O 3 , [24] Er: 3þ YAG, [25] and Nd 3þ :YAG [26] as well as ceramic phosphors such as Ce 3þ YAG, [27] Al 2 O 3 -Ce 3þ ,Gd 3þ :YAG, [28] and Mn 2þ : MgAl 2 O 4 . [29] Herein, we demonstrate a versatile single-step fabrication method of transparent ceramic composites by SPS.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Promising laser performance has been reported in various output wavelength, such as 2.7 μm Q-switch Er: Y 2 O 3 ceramic laser, 1.44 μm picosecond Nd: YAG ceramic laser and resonantly pumped eye-safe Er: YAG laser. [11][12][13] However, fabricating high-quality transparent ceramic for large-scale laser application is still challenging, which is necessary for high-power laser applications. [14] For the application as solid-state laser gain media, transparency is one of the key factors that affects the performance of laser gain media.…”
Section: Introductionmentioning
confidence: 99%